Reliability Centered Maintenance for electrical distribution system of Phontong substation in Vientiane Capital - O. Vilayphonh (2018)
© 2017 IEEE. This paper presents the Reliability Centered Maintenance methodology (RCM) for the maintenance of the distribution system of Phontong substation in Vientiane Capital, which is responsible for Electricité du Laos (EDL). The purposes of this study are distribution system reliability improvement and maintenance activities by using the RCM method. The RCM method has used the power interruption statistical data, activities of maintenance and appropriate maintenance activity selection. DIgSILENT PowerFactory 15.1 software is used in this study for analyzing the reliability indices of the distribution system. The result of maintenance plan based on principles of RCM has helped to reduce the number of outages under the budget maintenance cost, customer impact due to the power interruption. In additional, it also can help to decide the appropriate maintenance selection to improve the system reliability and minimize the interruption, failure in the distribution system.